PERSEPSI MASYARAKAT TENTANG PELAKSANAAN PROGRAM E-KTP DI KECAMATAN MOOAT KABUPATEN BOLAANG MONGONDOW TIMUR - PASEKI, MEISY VERONIKA; PANGKEY, MASJE; LONDA, VERY (Sam Ratulangi University, 2019)
The essence of e-KTP is one form of identity programmed online and is very helpful for theprocess of disclosing a crime, by getting instructions online through registration of population identitynumbers (NIK), where first there is a district / city code, date of birth and original number. These problemscan be grouped into three types of perceptions, namely: first perceptions about people's experience of EKTP,both perceptions of community knowledge about E-KTP, thirdly Perception regarding communityevaluation or evaluation of E-KTP. This study uses descriptive qualitative research methods. The researchinformants were 8 (eight) informants namely 1 sub-district head, 1 secretary, 1 ASN, 5 community members.Data collection techniques used are Interview Technique, Observation / Observation Technique, and DataAnalysis Technique used namely Data Reduction, Data Presentation, and Conclusion Withdrawal. Basedon the results of the research in Mooat Subdistrict, Bolaang Mongondow Timur Regency in the PublicPerception of the implementation of E-KTP in Mooat Subdistrict, Bolaang Mongondow Timur Regency asfollows: first, Perception Regarding Community Experience about E-KTP in the service process can beadequately handled and can be seen from the provisions - provisions or mechanisms in carrying out theprocess of providing services that are quite clear and directed, and making appropriate decisions with theissuance of special policies in minimizing delays in E-KTP services with a Record Certificate (SKP) whichhas the same function as E-KTP. Secondly, the Perception of Community Knowledge about E-KTP, can behandled enough that can be seen from the mechanism of E-KTP service delivery which is quite clear andalso provided a special section to provide information and direction from the leadership such as the servicesecretary to provide services equivalent to the services provided by banks. Third, Perception RegardingCommunity Evaluation or Evaluation of E-KTP in the service process has been adequately addressed andcan be seen from a special section to provide information to the community that came to receive servicesand supported by a fairly large and clear information board.Keyword : Perseption, Public, Implementation Of E-KTP Program